(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article provides data that this ridge-furrow method of sowing corn with a single application of nitrogen fertilizers reduces the number of treatments, has soil protection value, helps to preserve soil fertility, reduces its washout, and leads to an increase in yield. For the first time for the conditions of irrigation-eroded soils of the Samarkand region, a method and rates of nitrogen fertilization have been developed for ridge-furrow sowing of corn.